A Dataset of Ancient Chinese Math Word Problems and an Application for Research in Historic Mathematics - Keßler, Florian (Proceedings of the Second Workshop on Ancient Language Processing, 2025)
Solving math word problems, i.e. mathemati-cal problems stated in natural language, has re-ceived much attention in the Artificial Intelli-gence (AI) community over the last years. Unsurprisingly, research has focused on problems stated in contemporary languages. In contrast to this, in this article, we introduce a dataset of math word problems that is extracted from ancient Chinese mathematical texts. The dataset is made available. We report a baseline per-formance for GPT-4o solving the problems in the dataset using a Program-of-Thought paradigm that translates the mathematical pro-cedures in the original texts into Python code, giving acceptable performance but showing that the model often struggles with understanding the pre-modern language. Finally, we describe how the generated code can be used for research into the history of mathematics, by offering a way to search the texts by abstract op-erations instead of specific lexeme
Keywords: Chinese mathematics; math word problems; LLM